2015
DOI: 10.1007/s10531-015-0954-0
|View full text |Cite
|
Sign up to set email alerts
|

Human impact on tropical-alpine plant diversity in the northern Andes

Abstract: Conserving páramo diversity and ecosystem services in the northern Andes is urgent, and understanding factors that control vegetation changes is therefore crucial. Although anthropogenic activities have been common in the Andean highlands for centuries, the role of human influence in shaping páramo vegetation remains unclear. To assess the relative importance of human disturbance associated with cattle farming and cultivation for plant species diversity and composition, we analyzed variables driven by both nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
0
22
0
2
Order By: Relevance
“…As a result, while our results are bringing novel insight on the significant predictors of páramo plant richness, their explaining power remains relatively low and therefore, our interpretations should be handled accordingly. We believe important to focus future endeavors on additional potential richness drivers in the páramo such as the broad contemporary environment, past climate variations, disturbance variables, biome area, and biotic interactions for example (Sklenář and Ramsay, 2001;Cavieres et al, 2014;Vásquez et al, 2015). Finally, we consider that our results, despite the previously established drawbacks, advance important theories on páramo biogeography and the relevant but weak relationship between local plant richness and the macroclimate.…”
Section: Study Limitations and Future Recommendationsmentioning
confidence: 63%
See 1 more Smart Citation
“…As a result, while our results are bringing novel insight on the significant predictors of páramo plant richness, their explaining power remains relatively low and therefore, our interpretations should be handled accordingly. We believe important to focus future endeavors on additional potential richness drivers in the páramo such as the broad contemporary environment, past climate variations, disturbance variables, biome area, and biotic interactions for example (Sklenář and Ramsay, 2001;Cavieres et al, 2014;Vásquez et al, 2015). Finally, we consider that our results, despite the previously established drawbacks, advance important theories on páramo biogeography and the relevant but weak relationship between local plant richness and the macroclimate.…”
Section: Study Limitations and Future Recommendationsmentioning
confidence: 63%
“…When focusing on plant species richness, a decreasing tendency has been highlighted along the elevational gradient of certain páramos (Sklenár and Jørgensen, 1999;Sklenář and Ramsay, 2001) and latitudinal gradients remain generally understudied. Several authors have also discussed potential drivers of local species richness and found that human disturbance and several environmental factors, such as annual precipitation and scree, condition plant richness in the high tropical Andes (Sklenář and Ramsay, 2001;Vásquez et al, 2015;Cuesta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its remarkable biodiversity and high endemism, estimated at 60% of its flora ( Luteyn, 1999 ), the páramo is further known for contributing essential ecosystem services to local communities and cities such as Quito and Bogota, among which water provision and climate regulation, through carbon stocking, are particularly important ( Buytaert, Cuesta-Camacho & Tobón, 2011 ; Farley et al, 2013 ). Anthropogenic activities, including agriculture, farming and mining, have rapidly increased in extent and intensity for the past 50 years and now challenge the ecological resistance and resilience of the páramo ( Vásquez, Balslev & Sklenář, 2015 ). Climate change is also becoming a critical threat, especially near the nival altitudinal belt where species migration is limited ( Morueta-Holme et al, 2016 ), although there is yet much to understand about the adaptation capacity of páramo species.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is also becoming a critical threat, especially near the nival altitudinal belt where species migration is limited ( Morueta-Holme et al, 2016 ), although there is yet much to understand about the adaptation capacity of páramo species. To date, there is extensive research on páramo ecology that translates into numerous works on flora, fauna, biotope and ecosystems ( Ramsay & Oxley, 1996 ; Molinillo & Monasterio, 2002 ; Vásquez, Balslev & Sklenář, 2015 ). However, other important and related research fields, such as biogeography, remain understudied in the páramo and in tropical alpine regions in general ( Hoorn et al, 2010 ; Anthelme & Lavergne, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change may result in the migration, vulnerability or extinction of plant species by causing species distributions to shift, habitat fragmentation to increase, population sizes to decrease and genetic diversity to decline (Thuiller et al 2005, Heller and Zavaleta 2009, Bellard et al 2012, Diez et al 2012, Grimm et al 2013, Watson et al 2013. Furthermore, other human impacts are likely to cause additional habitat loss and threaten plant species (Tilman and Lehman 2001, Kier et al 2005, Vásquez et al 2015. In particular, threatened plants with narrow niche width and small population sizes may fail to adapt to novel climatic conditions and thus become endangered or even extinct (Bellard et al 2012, Botts et al 2013, Slatyer et al 2013.…”
Section: Introductionmentioning
confidence: 99%